Pengaruh Perasan Daun Belimbing Wuluh (Averrhoa bilimbi) Terhadap Pertumbuhan Bakteri Escherichia coli Patogen - Fitrotin Azizah (Universitas Muhammadiyah Surabaya, 2017)
abstract (Averrhoa bilimbi) is one of the plants that can be used as an antibacterial, good flowers, stems, leaves and stems have benefits and efficacy. Chemical constituents of the leaves starfruit are tannins, flavonoids, saponins. The active ingredient in the leaves starfruit is tannin. Escherichia coli is a bacterium that causes diarrhea. From the above discussion, the authors raised the theme of Influence starfruit juice of the leaves on the growth of pathogenic E. coli bacteria. Formulation of the problem researchers is whether there is influence starfruit juice of the leaves on the growth of Escherichia coli pathogens. This study aims to determine the concentration that could inhibit and kill Esherichia coli Escherichia coli. This research is experimental. The sample used is leaf green starfruit not so young in a fresh state taken in the area around the boarding author Sutorejo 11B stay. In this study, the sample size for each treatment as much as 3 100%, 90%, 80%, 70%, 60%, 50%, 40%, 30%, 20%, 10% and C (control). Independent variables are starfruit juice of the leaves, while the dependent variable growth of Escherichia coli. When the study carried out in January and July 2012. Data on the effect of starfruit juice of the leaves on the growth of Escherichia coli tested by laboratory examination and data collection techniques using Chi-Square 0:05. Based on the results it appears that at a concentration of 100% and 90% were able to kill the bacteria Escherichia coli, whereas the inhibitory power ranging from a concentration of 80%, 70%, 60%, 50%, 40%, 30%, 20%, 10%. From Chi-Square test was obtained λ2 count <of λ2 table. From this it turns out there leaves starfruit juice effect on the growth of Escherichia coli pathogenic bacteria.Keyword : Leaves starfruit, E. Coli